Life Cycle and Larval Feeding Habits of Macrostemum indistinctum Banks 1911 (Trichoptera: Hydropsychidae) in the Stream Flows into Krasiow Reservoir, Thailand - Khamrak, Orawan; Prommi, Taeng-On (Journal of Food Health and Bioenvironmental Science, 2023)
The aim of this work was to determine the feeding habits of Macrostemum indistinctum larvae using gut content analysis. The study was carried out in the stream flows into the Krasiow dam. A total of 126 larvae were captured and had the head capsule width measured. The gut content was analyzed under microscope. Seven categories of food items were determined: arthropod fragment, blue green algae, diatoms, gastropods, green algae, protozoa and rotifers. When comparing both populations in two seasons, statistically significant differences (P<0.05) were found for gastropods and protozoa. The food items, arthropods, blue green algae, diatoms, green algae and rotifers showed no difference between both populations. Macrostemum indistinctum was found to be an omnivorous collector organism. The similarities in the seasonal trophic structure might indicate the constant availability of food.